Barbecue Grill Workers Occupational Exposure to Particulate-Bound Polycyclic Aromatic Hydrocarbons - Oliveira, Marta (2019)
During a regular working day, grill workers are exposed to the emissions of charcoal-fired cooking activities, which include polycyclic aromatic hydrocarbons (PAHs) that are among the most health relevant compounds. Thus, in this work, the particulate matter at the breathing air zone of grill workers from a barbecue restaurant was sampled and the concentration of eighteen particulate-bound PAHs was determined by liquid chromatography with fluorescence and diode array detection. Median level of total PAHs (ΣPAHs) during 5 consecutive hours of exposure to barbecue fumes was 77.2 ng/m3 (maximum values of 261 ng/m3). Benzo(g,h,i)perylene, phenanthrene, and acenaphthylene were the most abundant compounds (82.7% of ΣPAHs). Levels of benzo(a)pyrene and total carcinogenic PAHs (naphthalene, benz(a)anthracene, benzo(b)fluoranthene, benzo(j)fluoranthene, benzo(k)fluoranthene, benzo(a)pyrene, chrysene, and indeno(1,2,3-cd)pyrene) varied between 0.03–0.79 ng/m3 and 2.10–36.7 ng/m3, respectively. Grill worker’s exposure to PAHs was well below the existent PAHs occupational threshold limit value of 200 µg/m3 proposed by the American Conference of Governmental Industrial Hygienists for an 8-h of exposure to coal tar pitch volatiles. Some preventive measures such as adequate maintenance of barbecue ventilation system, regular wash of workers exposed skin and the use of clean working clothes can contribute to reduce grill worker’s occupational exposure to PAHs.